Snowmen at night - Buehner, Caralyn; Buehner, Mark (New York : Phyllis Fogelman Books, 2002)
Snowmen play games at night when no one is watching.
NP
Keywords: Snowmen -- Juvenile fiction; Snowmen -- Fiction; Stories in rhyme